SEQUENCE OF TECTONIC DEFORMATION IN THE HISTORY OF VENUS: EVIDENCE FROM GLOBAL STRATIGRAPHIC RELATIONSHIPS - Head J.W.; Basilevsky A.T. (My University, 1998)
Analysis of local and regional stratigraphic relationships has permitted the assessment of the nature of tectonic structures and their distribution throughout the observed history of Venus, spanning the past several hundreds of millions of years. We find that shortening characteristic of intensely deformed tessera terrain gave way to widespread distributed fracturing and extension within the tessera and early post-tessera volcanic plains. This phase was followed by distributed deformation of the widespread younger volcanic plains involving compression to form broad ridge belts and closely following—and sometimes simultaneous—extension to form fracture belts. Emplacement of the most areally extensive regional volcanic plains exposed today was followed by widely distributed compression forming wrinkle ridges on the plains' surfaces. Focused extensional deformation (localized, linear rift systems) dominated the latest stages. These major temporal trends appear well established from a stratigraphic point of view and provide guidelines and constraints on models for the geologic history of Venus.